Polymyxin B Increases the Depletion of T Regulatory Cell Induced by Purinergic Agonist - Rojas-Pavez, J; Imarai-Bahamonde, C; Montoya-Kunsting, M; Acuna-Castillo, C (2012)
Regulatory T cells (Treg) are important in the development of immune tolerance under normal physiological conditions. However, in pathological situations such as cancer, Treg increases have been correlated with bad prognoses. Treg depletion can be achieved in vitro under several stimuli, including the activation of the purinergic P2X7 receptor. Our aim was to determine whether polymyxin B (PMB), which is a positive modulator of this receptor, could affect mice Treg depletion by ATP and related compounds. For that purpose, we evaluated by flow cytometry changes in Treg populations under several treatments with PMB and/or purinergic agonists and antagonists. We found that both ATP and NAD induce a dose-dependent decrease on the Treg CD4+ CD25+ population. PMB not only potentiated the effect of exogenous ATP and NAD, but also decreased the CD4+ CD25+ population when it was applied alone. While ATP mediated effects are related to the P2X7 receptor, PMB effects appear to be related to another mechanism. We conclude that PMB positively modulates the depletion of the CD4+ CD25+ population of Treg. Therefore PMB could constitute a non-canonical drug with potential use on Treg depletion and cancer treatment. © 2011.